High-level resistance to non-nucleos(t)ide reverse transcriptase inhibitor based first-line antiretroviral therapy in Ghana; A 2017 study - Parbie, Prince Kofi; Abana, Christopher Zaab-Yen; Kushitor, Dennis; Asigbee, Theodore Worlanyo; Ntim, Nana Afia Asante; Addo-Tetebo, Gifty; Ansong, Maclean Richard Darko; Ofori, Sampson Badu; Mizutani, Taketoshi; Runtuwene, Lucky Ronald; Nishizawa, Masako; Ishikawa, Koichi; et al. (Frontiers in Microbiology, 2022)
Expanding access to effective antiretroviral therapy (ART) is a major tool for management of Human Immunodeficiency Virus (HIV) infection. However, rising levels of HIV drug-resistance has significantly hampered the anticipated success of ART in persons living with HIV (PLWH), particularly those from Africa. Though great strides have been made in Ghana towards achieving the UNAIDS “95-95-95” target, a substantial number of PLWH receiving ART have not attained viral suppression. This study investigated patterns of drug resistance mutations in ART naïve as well as ART-experienced PLWH receiving first-line regimen drugs from Ghana. In a cross-sectional study, blood samples were collected from HIV-1 infected adults (≥18 years) attending HIV/AIDS clinic at the Eastern Regional Hospital, Koforidua, Ghana from September-October 2017. Viral RNA isolated from plasma were subjected to genotypic drug resistance testing for Protease Inhibitors (PI), Reverse Transcriptase Inhibitors (RTI) and Integrase Strand Transfer Inhibitors (INSTI). A total of 95 (84 ART experienced, 11 ART naïve) HIV-1 infected participants were sampled in this study. Sixty percent (50/84) of the ART-experienced participants were controlling viremia (viral load < 1,000 copies/mL). Of the 95 patient samples, 32, 34, and 33 were successfully sequenced for protease, reverse-transcriptase, and integrase regions, respectively. The dominant HIV-1 subtypes detected were CRF02_AG (70%), and A3 (10%). Major drug resistance associated mutations were only detected for reverse transcriptase inhibitors. The predominant drug resistance mutations were against nucleos(t)ide reverse transcriptase inhibitors (NRTI) - M184V/I and non-nucleos(t)ide reverse transcriptase inhibitors (NNRTI) - K103N. In the ART-experienced group, M184V/I and K103N were detected in 54% (15/28) and 46% (13/28) of individuals respectively. Both mutations were each detected in 33% (2/6) of ART naïve individuals. Multiclass resistance to NRTI and NNRTI was detected in 57% of ART-experienced individuals and two ART naïve individuals. This study reports high-level resistance to NNRTI-based antiretroviral therapy in PLWH in Ghana. However, the absence of major PI and INSTI associated-mutations is a good signal that the current WHO recommendation of Dolutegravir in combination with an NRTI backbone will yield maximum benefits as first-line regimen for PLWH in Ghana.